Edukasi Tempoyak sebagai Sumber Probiotik untuk Kesehatan Ibu dan Anak - Suci Rahmani Nurita (Jurnal Abdimas Kesehatan (JAK), 2022)
The infant morbidity rate is the second indicator in determining a child's health status because it reflects the baby's weak immune system. According to the 2018 Riskesdas National Report, the incidence of diarrhea in infants aged less than 1 year reached 9% (Kemenkes RI, 2019). Diarrhea is a disease with the second highest frequency worldwide after acute respiratory infections. Vighi et al (2008) stated that 70% of the body's immune system is influenced by the health of the digestive system. One effort to maintain digestive health can be done by consuming food or drinks that contain probiotics. Probiotics can be obtained from fermented foods and beverages. Tempoyak is a kind of traditional spontaneously fermented food made from durian (durio zibethinus) by wild microorganisms which is one of the local wisdom foods of the Jambi region. The education carried out targets an increase in the knowledge and attitudes of educational participants with the outputs in the form of educational media, activity reports and journal publications. Community service activities begin with problem identification, proposal making, licensing arrangements, time contracts, preparation of educational tools and materials, visits to PMB, explanation of educational materials, discussions and questions and answers. It can be concluded that there was a change in good knowledge and a positive attitude towards the target based on the results of the pre-post test analysis.